2015
DOI: 10.1155/2015/361604
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Kefir DerivedLactobacillus kefirion the Mucosal Immune Response and Gut Microbiota

Abstract: The evaluation of the impact of probiotics on host health could help to understand how they can be used in the prevention of diseases. On the basis of our previous studies and in vitro assays on PBMC and Caco-2 ccl20:luc reporter system presented in this work, the strain Lactobacillus kefiri CIDCA 8348 was selected and administrated to healthy Swiss mice daily for 21 days. The probiotic treatment increased IgA in feces and reduced expression of proinflammatory mediators in Peyer Patches and mesenteric lymph no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
108
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 75 publications
8
108
0
9
Order By: Relevance
“…Finally, when we analyzed Lactobacillus spp., we found a trend toward increase in CTR-Lk mice, similarly to the significant increase previously reported by our group [29]. It is worth to note that some of these results do not completely agree with Carasi et al (2015) [29], which could be mostly related to the difference in the length of L. kefiri treatment (3 weeks vs. 6 weeks). Overall, these changes in microbiota populations may explain in part the anti-inflammatory and metabolic improvements generated by L. kefiri in Lk-treated mice.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, when we analyzed Lactobacillus spp., we found a trend toward increase in CTR-Lk mice, similarly to the significant increase previously reported by our group [29]. It is worth to note that some of these results do not completely agree with Carasi et al (2015) [29], which could be mostly related to the difference in the length of L. kefiri treatment (3 weeks vs. 6 weeks). Overall, these changes in microbiota populations may explain in part the anti-inflammatory and metabolic improvements generated by L. kefiri in Lk-treated mice.…”
Section: Discussionsupporting
confidence: 84%
“…F. nucleatum is known to cause colon cancer by adhering to the colon epithelium and causing cell mutation. L. kefiri, L. kefiranofaciens and L. kefirgranum, which were proven by recent studies to have strong probiotic properties and positive health effects, are only present in kefir grains [14,15,16,17,18]. Moreover, the Saccharomyces and Kluyveromyces yeast strains unique to kefir grains also have important probiotic properties and antimicrobial effects that were observed in recent studies [19,20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Kefir grains are constituted by a complex microbial community containing species of lactic and acetic acid bacteria and yeasts, and they are used to obtain a fermented milk named kefir [9,34,35]. Recent microbiological analysis of kefir grains being consumed in our region (Grand Vitoria, Brazil) [36,37] showed a microflora formed by beneficial bacteria (e.g., Lactobacillus kefiranofaciens, Bifidobacterium) and yeasts (e.g., Candida kefir) which have been shown to preserve gut eubiosis and correct dysbiosis by adhering to gastrointestinal mucus [31,38]. These beneficial microbes then protect against the invasion of pathogenic microbes [7,39,40] and against the cytotoxic effects of pathogenic microbial toxins [41].…”
Section: Functional Foods and Kefirmentioning
confidence: 99%
“…Kefir consumption results in transient changes in the levels of cytokines [92][93][94], TNFα and INFγ, in both in vivo [83,84] and in in vitro experiments [93]. Several studies with whole kefir, kefir fractions, or organisms isolated from kefir demonstrated that anti-inflammatory cytokines promote a Th2 response while simultaneously inhibiting the pro-inflammatory Th1 response [39,78,[92][93][94][95].…”
Section: Anti-atherosclerotic and Anti-inflammatory Effectsmentioning
confidence: 99%